2015
DOI: 10.14740/jocmr1975e
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Epidemiological Aspects and Mortality of Alcoholic Liver Disease in Korea in the Decade Between 2000 and 2009

Abstract: BackgroundAlcohol consumption and related alcohol liver disease (ALD) have substantially increased in Korea during the last decade. The objective of this study was to evaluate the trends in the epidemiological aspects and mortality rate (MR) of Korea in the decade between 2000 and 2009.MethodsThe raw data analyzed in this study were obtained from the website of “the ALD” managed by Korea Center for Disease Control and Prevention (KCDC), Korea Public Health Association (KPHA), and statistics website of Statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The prevalence of alcoholic liver cirrhosis in cirrhosis population was increased by 43% in 7 years in the USA [ 6 ]. The number of deaths from ARLD in South Korea increased from 1403 to 3588 between 2000 and 2009 [ 7 ]. These studies suggested that the burden of ARLD is increasing gradually.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of alcoholic liver cirrhosis in cirrhosis population was increased by 43% in 7 years in the USA [ 6 ]. The number of deaths from ARLD in South Korea increased from 1403 to 3588 between 2000 and 2009 [ 7 ]. These studies suggested that the burden of ARLD is increasing gradually.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol consumption (ethanol in g/day) was defined as the frequency of alcohol consumption multiplied by the number of alcoholic drinks per day. 27 The mean alcohol consumption was computed and categorized as <5 g/day, 5–9.9 g/day, 10–19.9 g/day, 20–29.9 g/day, and ≥30 g/day. Data on other covariates were obtained from the most recent year that the data were available within the look‐back period.…”
Section: Methodsmentioning
confidence: 99%
“…Given that ALD develops as a result of long‐term alcohol consumption, we attempted to capture the longest duration of alcohol consumption by indicating its mean value during the look‐back period. Alcohol consumption (ethanol in g/day) was defined as the frequency of alcohol consumption multiplied by the number of alcoholic drinks per day 27 . The mean alcohol consumption was computed and categorized as <5 g/day, 5–9.9 g/day, 10–19.9 g/day, 20–29.9 g/day, and ≥30 g/day.…”
Section: Methodsmentioning
confidence: 99%
“…Alcohol consumption per day was calculated based on the frequency of alcohol consumption multiplied by the number of alcohol drinks per day (amount of alcohol from soju using standard ethanol concentration 20% in one bottle of soju). It was categorized into four groups as 0, < 12.5, 12.5–49, or ≥ 50 ethanol in grams per day 38 . Lifetime alcohol consumption was calculated by the mean of alcohol grams per day collected from multiple health examinations during the study period between 2002 and 2018.…”
Section: Methodsmentioning
confidence: 99%